Financial challenges and sustainable management practices among women enterprise owners in Malaysia: a thematic analysis for long-term stability - Abdull Rahman, Nurul Labanihuda; Wan Mustapa, Wan Nurulasiah; Rozali, Ahmad Zulhusny; Abdul Pisal, Nadhilah; Yahya, Norziana (Frontiers in Applied Mathematics and Statistics, 2025)
PurposeThis article explores the key factors contributing to ineffective financial management among women enterprise owners in Malaysia that lead to cash flow problems, debt accumulation, reduce profitability, limited growth opportunities, increased risk, and enterprise failure.Design/methodology/approachThrough in-depth interviews with women enterprise owners, this study explores the contributing factors to the ineffective financial management by women enterprise owners. A thematic analysis is then applied to identify the recurring themes and patterns within the data, providing a comprehensive understanding of the ineffective financial management.FindingsThis study identifies lack of customers, weak financial records, rising prices of raw materials, lack of sales, limited financial training, and supplier fraud as the factors contributing to the weaknesses of financial management among women enterprise owners in Malaysia.Originality/valueThis study offers original insights into the key factors behind ineffective financial management among women enterprise owners in Malaysia, using qualitative methods to uncover practical challenges and context-specific issues such as supplier fraud and limited financial education. Thus, future research should focus on validating the identified factors, evaluating financial education programs, exploring digital tools, examining sector-specific challenges, and assessing government policies supporting financial management of enterprises.